Testes utilizados para avaliação da capacidade funcional em transplantados renais. uma revisão sistemática - Silva, Graziella Alves da (2021)
Kidney transplant patients present musculoskeletal and functional capacity changes. There is a wide variety of tests available to assess functional capacity, but there is no specific test for the chronic kidney population. Objective: This review aims to identify which tests are used to assess functional capacity in kidney transplant recipients. Material and Methods: This systematic review follow PRISMA guidelines and is registered in PROSPERO. Study quality was assessed by RoB2, ROBINS I and Newcastle-Ottawa. Results: Thirty-one studies were included in this review, 7 randomized, 14 non-randomized and 10 observational. The tests found were ISWT (5%), TUG (3%), GUG (3%), STS60 (13%), 30CST (30%), CPET (49%), SPPB (5%) and 6MWT (21%). No randomized and non-randomized studies had a low risk of bias and in observational studies, none had a high risk of bias. Conclusion: In the last decade, has a significant increase in studies that performed the assessment of functional capacity in transplant recipients, with an increase in the variety of tests used as well, but a major limitation since there are no studies to validate tests in transplant recipients and no studies that evaluated the accuracy of the tests in this population. Complementary assessments bring greater quality to studies.